2017
DOI: 10.1016/j.cell.2017.06.051
|View full text |Cite
|
Sign up to set email alerts
|

An Engineered orco Mutation Produces Aberrant Social Behavior and Defective Neural Development in Ants

Abstract: Summary Ants exhibit cooperative behaviors and advanced forms of sociality that depend on pheromone-mediated communication. Odorant receptor neurons (ORNs) express specific odorant receptors (ORs) encoded by a dramatically expanded gene family in ants. In most eusocial insects, only the queen can transmit genetic information, restricting genetic studies. In contrast, workers in Harpegnathos saltator ants can be converted into gamergates (pseudoqueens) that can found entire colonies. This feature facilitated CR… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
215
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 195 publications
(235 citation statements)
references
References 74 publications
5
215
1
1
Order By: Relevance
“…If this model is correct, then this orco dependent stage of glomerulus expansion could represent an evolutionary change in the development of ants relative to flies that is related to the evolution of expanded OR repertoires. Inspired by our initial findings, colleagues decided to also examine brains of a second ant species in which they had generated an orco mutant, and they found an antennal lobe phenotype similar to what we had observed in O. biroi (reported in this issue of Cell, Yan et al, 2017). These results further indicate that the role of orco in neuro-anatomy is likely conserved throughout the ants.…”
Section: Discussionmentioning
confidence: 66%
“…If this model is correct, then this orco dependent stage of glomerulus expansion could represent an evolutionary change in the development of ants relative to flies that is related to the evolution of expanded OR repertoires. Inspired by our initial findings, colleagues decided to also examine brains of a second ant species in which they had generated an orco mutant, and they found an antennal lobe phenotype similar to what we had observed in O. biroi (reported in this issue of Cell, Yan et al, 2017). These results further indicate that the role of orco in neuro-anatomy is likely conserved throughout the ants.…”
Section: Discussionmentioning
confidence: 66%
“…In addition, these ants were largely missing their antennal lobe glomeruli. 101,102 This study is an addition to the knowledge of the olfactory mechanism in rice planthoppers. Odorant binding proteins are important for binding odorants and in rice-plant seeking behavior.…”
Section: Discussionmentioning
confidence: 99%
“…The results are similar to recent studies in which Orco knockout ants Harpegnathos saltatory were completely unaware of chemical cues, becoming asocial, leaving their nests, and not foraging for food. In addition, these ants were largely missing their antennal lobe glomeruli …”
Section: Discussionmentioning
confidence: 99%
“…It is now appreciated the striking functions of insect Orco in odorant perception, reproductive physiology, and social behavior plasticity. 24 In this study, we identified the gene encoding Orco protein of SBPH L. striatellus. The sequence alignment and homology analysis demonstrated significant conservation of Orco among different order insects, which were separated by millions of years on the evolutionary scale.…”
Section: Discussionmentioning
confidence: 99%
“…Orco is also required for OR trafficking past the ciliary constriction into the outer dendrites . In addition, knockout or mutation of Orco gene has also revealed that Orco is required for insect olfaction . In ants, Orco mutagenesis also impaired neural development .…”
Section: Introductionmentioning
confidence: 99%